TINGKAT KEPUASAN KONSUMEN TERHADAP MIE CHE BA TAHUNA DI KELURAHAN SAWANG BENDAR KECAMATAN TAHUNA KABUPATEN KEPULAUAN SANGIHE - Lahinda, Varah Claudya Cristin; Ruauw, Eyverson; Ngangi, Charles Reijnaldo (AGRI-SOSIOEKONOMI, 2022)
The purpose of this research was to determine the level of consumer satisfaction with "Mie Che Ba Tahuna" at Sawang Bendar Sub-District, Tahuna District, Sangihe Islands Regency. This research was conducted from September to December 2021. The data used in this study were primary data and secondary data. The sampling methods used in this study is accidental sampling. Primary data obtained from interviews and direct observation. Interviews were conducted on the owner of the “Mie Che Ba Tahuna” Restaurant and the consumers who visited the Mie Che Ba Tahuna Restaurant. Questionnaires were distributed to consumers as respondents as many as 45 people. Secondary data obtained from various sources, namely literature studies including books, internet, journals and the results of previous research. The data analysis used is descriptive data analysis using a Likert scale. The results of this research showed that the overall level of consumer satisfaction with "Mie Che Ba Tahuna" in Sawang Bendar Sub-District, Tahuna District, Sangihe Islands Regency was classified as satisfied with a consumer satisfaction index of 79.86%.